Boosting cross-border regions through better cross-border transport services. The European case - Medeiros, E. (2021)
Cross-border regions are the laboratories of European integration. Daily interactions across European borders let citizens experience the benefits of the European Union (EU) internal market. Still, many border barriers continue to prevent individuals and organisations from exploiting the full-potential of European border regions and the benefits of a more integrated European territory. Amongst these barriers are the absence or inappropriate supply of cross-border public transport services. In this context, this paper presents potential policy tools to increase border permeability related to cross-border public transport as well as practical results from a few case-studies implemented across Europe.